Breast thermography: a systematic review and meta-analysis - Ane Goñi-Arana; Jorge Pérez-Martín; Francisco Javier Díez (Systematic Reviews)
Abstract Background Breast thermography originated in the 1950s but was later abandoned due to the contradictory results obtained in the following decades. However, advances in infrared technology and image processing algorithms in the twenty-first century led to a renewed interest in thermography. This work aims to provide an updated and objective picture of the recent scientific evidence on its effectiveness, both as a screening and as a diagnostic tool. Methods We searched for clinical studies published between 2001 and May 31, 2023, in the databases PubMed and Scopus, that aimed to evaluate the effectiveness of digital, long-wave infrared imaging for detecting breast cancer. Additional documents were retrieved from the studies included in the systematic reviews that resulted from the search and by searching for the names of commercial systems. We limited our selection to studies that reported the sensitivity and specificity of breast thermography (or the data needed to calculate them) using images collected by themselves, with at least five breast cancer cases. Studies that considered breast diseases other than cancer to be positive or that did not use standard tests to set the ground truth diagnosis were excluded, as well as articles written in a language other than English and documents we could not access. We also conducted meta-analyses of proportions of the sensitivity and specificity values reported in the selected studies and a bivariate meta-analysis to account for the correlation between these metrics. Results Our systematic search resulted in 22 studies, with an average pooled sensitivity and specificity of 88.5% and 71.8%, respectively. However, the differences in patient recruitment, sample size, imaging protocol, equipment, and interpretation criteria yielded a high heterogeneity measure (79.3% and 99.1% $${I}^{2}$$ I 2 value, respectively). Conclusions Overall, thermography showed a high sensitivity in the selected studies, whereas specificity started off lower and increased over time. The most recent studies reported a combination of sensitivity and specificity comparable to standard diagnostic tests. Most of the selected studies were small and tend to include only patients with a suspicious mass that requires biopsy. However, larger studies with a wider variety of patient types (asymptomatic, women with dense breasts, etc.) have been published in the latest years.